A Privacy Attack on Multiple Dynamic Match-key based Privacy-Preserving Record Linkage - Vidanage, Anushka; Ranbaduge, Thilina; Christen, Peter; Randall, Sean (Swansea University, 2020)
Over the last decade, the demand for linking records about people across databases has increased in various domains. Privacy challenges associated with linking sensitive information led to the development of privacy-preserving record linkage techniques. The multiple dynamic match-key encoding approach recently proposed by Randall et al. (IJPDS, 2019) is such a technique aimed at providing sufficient privacy for linkage applications while obtaining high linkage quality. However, the use of this encoding in large databases can reveal frequency information that can allow the re-identification of encoded values.